Designing an online intervention for adults with addictive eating: a qualitative integrated knowledge translation approach. Issue 6 (7th June 2022) - Leary, Mark; Pursey, Kirrilly; Verdejo-García, Antonio; Skinner, Janelle; Whatnall, Megan C; Hay, Phillipa; Collins, Clare; Baker, Amanda L; Burrows, Tracy
Abstract : Introduction: Codesign is a meaningful end-user engagement in research design. The integrated knowledge translation (IKT) framework involves adopting a collaborative research approach to produce and apply knowledge to address real-world needs, resulting in useful and useable recommendations that will more likely be applied in policy and practice. In the field of food addiction (FA), there are limited treatment options that have been reported to show improvements in FA symptoms. Objectives: The primary aim of this paper is to describe the step-by-step codesign and refinement of a complex intervention delivered via telehealth for adults with FA using an IKT approach. The secondary aim is to describe our intervention in detail according to the TIDieR checklist. Design: This study applies the IKT process and describes the codesign and refinement of an intervention through a series of online meetings, workshops and interviews. Participants: This study included researchers, clinicians, consumers and health professionals. Primary outcome measure: The primary outcome was a refined intervention for use in adults with symptoms of FA for a research trial. Results: A total of six female health professionals and five consumers (n=4 female) with lived overeating experience participated in two interviews lasting 60 min each. This process resulted in the identification of eight barriers and three facilitators to providing and receiving treatment for FA, eight components needed or missing from current treatments, telehealth as a feasible delivery platform, and refinement of key elements to ensure the intervention met the needs of both health professionals and possible patients. Conclusion: Using an IKT approach allowed for a range of viewpoints and enabled multiple professions and disciplines to engage in a semiformalised way to bring expertise to formulate a possible intervention for FA. Mapping the intervention plan to the TIDieR checklist for complex interventions, allowed for detailed description of the intervention and the identification of a number of areas that needed to be refined before development of the finalised intervention protocol.